Field measurement of glyphosate and AMPA in the deposited sediment on the central-semiarid region of Argentina - Avecilla, Fernando; Panebianco, Juan Esteban; de Oro, Laura Andrea; Aparicio, Virginia Carolina; Mendez, Mariano Javier (Elsevier, 2025)
In the central semiarid region of Argentina (CSRA), agricultural soils coexist with remaining patches of native forest. Glyphosate is used on agricultural soils, but the presence of glyphosate and its main metabolite (aminomethylphosphonic acid, AMPA) in fallen dust have not been evaluated in the CSRA. The presence and concentration of glyphosate and AMPA were evaluated in the sediment collected in a forest patch (FR) and on a surrounding agricultural soil (AG) during 2021. Glyphosate and AMPA were detected in all samples of sediments on FR and AG. The concentration of glyphosate in the sediment ranged from 16.8 to 192.7 μg kg−1 and the concentration of AMPA ranged from 31.9 to 210.3 μg kg−1. Sediment deposited on AG showed a higher concentration of glyphosate and AMPA than that deposited on FR. The highest concentrations of glyphosate and AMPA were found in the second semester of the year (spring and early summer), when glyphosate is used intensively for weed control and wind erosion risk is higher. Our results show that the sediment generated by wind erosion, rural traffic and tillage could be a route for glyphosate and AMPA to enter into ecosystems and areas where the herbicide is not used.